Multicultural child care - Vedder, Paul (Bilingual education and bilingualism, 1996)
"What is the state of multicultural education in child care centres in Western European countries? What should multicultural education in these centres look like? These are the two key questions addressed in this book. In this study the authors have analysed the state of multicultural education in child care centres in the Netherlands, England, Scotland, Denmark, Sweden, Germany, Belgium, France and Spain. The main situation considered here is the Netherlands where the recent and rapid growth of the number of child care centres, together with the growing numbers of immigrant children visiting these centres, have given a strong impetus to concerns about the quality of centre education from a multicultural perspective." "For centre staff, sensitive responses towards children and parents, as well as parental involvement, have become essential for managing cultural diversity in a way beneficial for both migrant and indigenous families. It is argued that defining and improving the quality of centre education from a multicultural perspective require discussions between staff and parents about educational goals and the means to achieve them. The book gives recommendations for improving the relationship between staff and parents by way of consensus building about these aims."--Jacket